2003
DOI: 10.1002/jbm.a.10158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multigrooved surfaces on osteoblast‐like cells in vitro: Scanning electron microscopic observation and mRNA expression of osteopontin and osteocalcin

Abstract: This study evaluated the behavior of osteoblast-like cells on multigrooved surfaces consisting of a combination of microgrooves and macrogrooves. A polystyrene substrate was fabricated with multigrooves with 90-degree, V-shaped microgrooves with a 2-microm pitch cut on trapezoidal macrogrooves, which had a 50-microm ridge width, a 50-microm wall width, a 50-microm bottom width, and 25-microm depth. Smooth polystyrene substrates were also prepared as controls. Rat bone marrow cells were cultured as osteoblast-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 40 publications
7
39
0
Order By: Relevance
“…Scanning electron microscopy demonstrated that with the increased grain size, the width and the depth of the abrasions obtained on the surface increased ( Figure 1A, B) while abrasion density decreased ( Figure 1C). AFM analysis indicated that the abrasions were V-shaped, although they were significantly less uniform that abrasions prepared previously by micromachining [27,28] and microfabrication [17] techniques.…”
Section: Abraded Surfaces As a Model System For Study Of Topographicamentioning
confidence: 63%
“…Scanning electron microscopy demonstrated that with the increased grain size, the width and the depth of the abrasions obtained on the surface increased ( Figure 1A, B) while abrasion density decreased ( Figure 1C). AFM analysis indicated that the abrasions were V-shaped, although they were significantly less uniform that abrasions prepared previously by micromachining [27,28] and microfabrication [17] techniques.…”
Section: Abraded Surfaces As a Model System For Study Of Topographicamentioning
confidence: 63%
“…In this study, osteopontin and osteocalcin mRNA expression was higher in the experimental groups than in the control group. Osteopontin and osteocalcin are wellknown markers of bone-related cell differentiation [14][15][16]21) . In particular, osteopontin is a marker of osteoblast or odontoblast differentiation 21) .…”
Section: Discussionmentioning
confidence: 99%
“…Microstructured titanium surfaces favored mesenchymal stem cell differentiation towards the osteoblastic lineage [16]. On a surface with grooves, osteoblastic cells expressed a higher RNA level of osteopontin and osteocalcin than on a flat surface [19]. Experiments using defined sizes of pits demonstrated that activity of alkaline phosphatase as a marker for osteogenic differentiation was more stimulated on 11 nm islands compared with 85 nm islands [20].…”
Section: Cell Regulation By Physical Characteristics Of a Materials Tomentioning
confidence: 99%